Perancangan Standar Operasional Prosedur (SOP) Pada Sistem Persediaan di PT. XYZ - Pramesta Minfathul Cahyani; Mochamad Sulaiman (Journal of Industrial Innovation and Safety Engineering (JINSENG), 2024)
The application of performance management is very influential in knowing the performance of a performance system. Standard operating procedures (SOP) can affect the existing performance system in the company. This is because standard operating procedures are intended as a basic reference in the implementation of the production process in the event of an error or violation. The existence of SOPs helps in finding production errors. This research is located at PT. XYZ, which is one of the support offices engaged in the overhaul of heavy equipment components. The preparation of the SOP was motivated by the need to clarify the workflow on updating the gudang inventory system and to emphasize the concept of existing collaboration. The preparation of the SOP uses the swimlane diagram method. Swimlane diagram is an activity diagram to represent an activity by showing the actors involved in it which is described as a swimming pool path. This study uses a qualitative data approach, data collection is done by direct observation in the field, and interviews. The results of the study there are 8 stages of the work process on the inventory system of PT. XYZ and with the preparation of SOPs using swimlane diagrams, there are parties or actors who are directly related to the inventory system of PT. XYZ which consists of 2 pools and 5 lanes. Pool 1 is a production department consisting of 2 lanes, namely the perencanaan team and the demolition department. Pool 2 is an inventory department consisting of 3 lanes, namely gudang team, inventory team, and purchasing.